Developing Interactive Media Based on Problem-Based Learning to Improve Students' Mathematical Understanding - Harahap, Delviananda; Siregar, Tiur Malasari (Jurnal Analisa, 2025)
This study aims to develop interactive learning media based on Problem Based Learning to improve students' mathematical understanding. The type of research used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results of the study indicate that the development of interactive media based on problem based learning to improve students' mathematical understanding is stated as 1) Valid, with an average score of 92.7% (81%≤x≤100%) included in the very valid category, 2) Practical, based on the teacher response questionnaire given to two teachers, an assessment of 98% (81%≤x≤100%) is classified as very practical, and based on the student response questionnaire, an assessment of 87.21% is classified as very practical. 3) Effective, this is reviewed based on classical learning completion of 88.2% (≤85% of students obtained a score of ≥76) included in the effective category, the achievement of mathematical understanding indicators is reviewed from the increase from pretest to posttest in each indicator of mathematical understanding used.